High cycle fatigue life estimation of AlSi10Mg processed by laser powder bed fusion - Hovig Even W.; Azar Amin S.; Sunding Martin F.; Sørby Knut; M'hamdi Mohammed; Andreassen Erik (MATEC Web of Conferences, 2018)
Fatigue life is known to be dependent on the surface properties of the material. Surface roughness provokes local stress concentration and cause crack initiation even at minute cyclic loads. In laser powder bed fusion, the as-built surfaces show variable roughness depending on the orientation of the specimens with respect to the build plate. In order to analyse the effect of build angle on surface properties, flat tensile specimens were produced from an AlSi10Mg alloy in a Concept Laser M2 Cusing machine. Seven specimens were arranged from flat to perpendicular with respect to the build plate at 15° intervals. The as-built surface topography of each specimen was characterised by white light interferometry. Two methods for calculating the stress concentration factor for high cycle fatigue simulation were developed. The presence of subsurface porosity was a crucial factor in expanding the stress concentration as demonstrated by finite element analysis.